ANALISIS PERBANDINGAN USAHATANI KELAPA SAWIT POLA SWADAYA DI LAHAN GAMBUT PASANG SURUT DAN LAHAN MINERAL DI KOTA DUMAI - Ruth Agustine Putri Zendrato; Syaiful Hadi; Novian Novian (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2022)
Dumai city is one of the cities in Riau Province, which has potential in the field of oil palm plantations. The development of oil palm in Dumai city due to the increasing demand for palm oil, so that the use of mineral land is more and more limited. This led to many farmers who began to seek the development of oil palm plantations using peat and tidal peat. This study aims to analyze the comparison of productivity, cost of production and net income of oil palm smallholders independent patterns in tidal peatlands and mineral land in Dumai city. The research method used quantitative statistical analysis is to calculate productivity, production costs, revenues, and analyze the comparison of productivity, production costs and revenues in mineral land and tidal peatlands with statistical T test of independent samples. The results showed that the productivity of fresh fruit bunches, production costs and net income of planters between the two lands in Dumai were statistically significantly different. The largest productivity of fresh fruit bunches of oil palm is in mineral land at 16.18 tons/ha/year and the smallest tidal peat at 12.04 tons/ha/year. The largest palm oil production costs are in tidal peatlands of Rp.709.54 Kg/year and mineral land of Rp.521.88 Kg/year. The net income of oil palm planters in Dumai city on mineral land amounted to Rp.13,372,158/ha/year and on Tidal peatlands amounting to Rp.7,724,441 ha/year. Keywords: Oil palm, farming, mineral land, tidal peat land.